2004
DOI: 10.1590/s0036-46652004000100012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular profile after intravenous injection of Africanized bee venom in awake rats

Abstract: SUMMARYThe manifestations caused by Africanized bee stings depend on the sensitivity of the victim and the toxicity of the venom. Previous studies in our laboratory have demonstrated cardiac changes and acute tubular necrosis (ATN) in the kidney of rats inoculated with Africanized bee venom (ABV). The aim of the present study was to evaluate the changes in mean arterial pressure (MAP) and heart rate (HR) over a period of 24 h after intravenous injection of ABV in awake rats. A significant reduction in basal HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…65 In another rat study, injection of bee venom decreased renal blood flow and glomerular filtration rate. 66 Renal blood flow returned to normal within 24 h, but glomerular filtration rate remained decreased.…”
Section: Pathophysiologymentioning
confidence: 96%
See 1 more Smart Citation
“…65 In another rat study, injection of bee venom decreased renal blood flow and glomerular filtration rate. 66 Renal blood flow returned to normal within 24 h, but glomerular filtration rate remained decreased.…”
Section: Pathophysiologymentioning
confidence: 96%
“…The mechanisms of renal injury were believed to be decreased renal blood flow, myoglobinuria, hemoglobinuria and direct tubular toxicity. [65][66][67] Pathology In patients with nephrotic syndrome or proteinuria after bee sting, the renal pathological changes include minimal change disease, mesangial proliferative glomerulonephritis, membranous glomerulonephritis and glomerulosclerosis; tubular necrosis, interstitial nephritis and vasculitis have also been reported after bee sting. [30][31][32]57 Glomerular deposition of complement component C3, IgM and IgG has been demonstrated.…”
Section: Pathophysiologymentioning
confidence: 99%
“…This vasorelaxation mechanism may be negatively regulated by nitric oxide 44 . Recent studies conducted by Guimarães et al 43 concluded that the fall in mean arterial pressure is probably due to several factors, in addition to the cardiac changes already demonstrated in Wistar rats; it is possible that the venom components themselves or even substances released in the organism play some role in peripheral arteriolar resistance and may contribute to the changes in mean arterial pressure.…”
Section: Anatomopathological Examinationmentioning
confidence: 99%
“…The presence of different molecules in the venom, including phospholipase A2, hyaluronidase, melittin, apamine [37][38][39][40] , and, most recently, a serine protease-like protein studied by Lima et al 41 , may contribute to skin necrosis at the sting site. Such necrosis has frequently occurred and has been reported by most studies in Brazil [33][34][35][36][37][38][39][40][41][42][43][44][45] . The presence of rhabdomyolysis characterized by fiber eosinophilia, vacuolization, and absence of nuclei can be seen in Figure 1B.…”
Section: Anatomopathological Examinationmentioning
confidence: 99%
“…In recent years, much attention on bee sting-related deaths has been focused on the African Apis mellifera scutellata subspecies, the so-called "killer bee," which attacks in larger numbers, with much less provocation and with greater persistence than European honey bees (Guimarães et al, 2004;Vetter et al, 1999;Reis et al, 1998). Africanized bees are hybrids between African and European bees, which display a well-developed defensive behavior, attacking their victims in swarms and inoculating large amounts of venom (Vetter et al, 1999).…”
Section: Resultsmentioning
confidence: 99%